Conodonts from the Early Triassic microbialite of Guangxi (South China): implications for the definition of the base of the Triassic System. (25th March 2015) - Brosse, Morgane; Bucher, Hugo; Bagherpour, Borhan; Baud, Aymon; Frisk, Åsa M.; Guodun, Kuang; Goudemand, Nicolas
Abstract: We describe a new Early Triassic (Griesbachian) succession of conodont faunas from a high‐resolution sampling of the basal Early Triassic microbial limestone and the base of the overlying unit at the Wuzhuan section (Nanpanjiang Basin, Guangxi, South China). The microbial limestone records the earliest phase of the Early Triassic biotic recovery after the end‐Permian mass extinction. For the first time, rich conodont faunas are reported from within the microbialite. The faunas from Wuzhuan are largely dominated by anchignathodontids, including several Isarcicella species, which were previously documented only from strata above the microbialite. A total of 14 conodont species assigned to three genera is recorded from the Wuzhuan section. Starting from the base of the microbialite upwards, several species are sequentially added to the conodont assemblage. The alpha diversity peaks at the top of the microbialite. The conodont record in the considered microbialite interval at Wuzhuan is presumably unaffected by local ecological changes. It therefore more likely represents an evolutionary rather than an ecological pattern. We compare the Wuzhuan's conodont record with a well‐supported phylogenetic model and suggest that the sequence of first occurrences at Wuzhuan is the closest to the 'true' sequence of evolutionary events that took place during this Griesbachian radiation of anchignathodontids. Based on comparisons with the GSSP section at Meishan, we suggest further that the first occurrence of Hindeodus parvus in Meishan does not correspond to its first appearance datum.